Tolerance of Soybean Rhizobia to Soil Acidity 1 - Jones, R. A.; Giddens, J. E. (1985)
Some nodule bacteria do not tolerate acid soils. A study was initiated to determine if Rhizobium japonicum could adapt to soil acidity and therefore become more effective N z-fixers in association with soybeans (Glycine max L. Merr.) grown in acidic soils. Nodules were obtained from soybeans grown in fields where the crop had been planted for at least 5 years in soil with pH near 5, 6 or 7. The nodular material was used for inoculation of soybeans in a factorial experiment grown in methyl bromide fumigated soil obtained from the same fields as the inoculum. Nitrogenase activity (C zH z - C zH 4reduction) and plant weight were usedfor evaluating the treatment effects. The results seem to indicate that the nodular bacteria did not adapt to a given soil pH. Soybeans grown in soil at pH 6 grew best regardless of whether inoculum was from plants grown at pH 5, 6 or 7. In acid soil, inoculum from soils at pH 5 was no better than those from pH 6 or 7.